Groundwater condition of Banepa area, Central Nepal - Shrestha, Suresh; Shrestha, Suresh Das (Bulletin of the Department of Geology, 2008)
Only surface water has been distributed in the Banepa Municipality area, Central Nepal by Nepal Water Supply Corporation (NWSC) and is not sufficient as per the demand of public. A hydrogeological study was made to know the groundwater potential of the area. Banepa lies entirely in the Lesser Himalaya and constitutes consolidated phyllite and metasandstone basement rocks, and Quaternary sediment of gravel, sand and carbonaceous clay deposited in the valley. The thickness of sediment ranges from 20 to 40 m, of which gravel, sand and clay individually approach upto 20, 5 and 15 m, respectively. Transmissivity of the aquifer varies from 0.8 to 3.15 m2/day. Hydraulic conductivity varies from 0.022 to 0.14 m/day and specific capacity varies from 1.2 to 72 m3/day/m in the study area. The thickness of the aquifer is low and the hydraulic properties are also not favorable to extract sufficient quantity of groundwater in Banepa area. Therefore, an alternative source of water supply should be explored to fulfill present and future water demand.   doi: 10.3126/bdg.v11i0.1540 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 31-40